THE EVALUATION OF TEACHER TRAINING AND EDUCATION PROGRAM OF RAYON 118 UNIVERSITY OF PALANGKA RAYA - Manalu, Sanggam Roy I.; Arifin (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
This research aims to evaluate the performance of Teacher Training and Education Program of Rayon 118 conducted by University of Palangka Raya. The analysis includes context, input, process, and products of the program. The results to be achieved: (1) description and documents to support the context, input, process and the products of the program, (2) the challenges of the implementation of the program, and (3) the alternatives of solution for the challenges of the program. This research also uses program evaluation design for Context, Input, Process, and Product model. Based on the result of the research, it can be concluded as follows: (1) on the Context component, the policies and the purposes of the program already have a clear law foundation; (2) on the Input component, it is acknowledged that: a) the participants of the program are the state school and private-school teachers who had been eligible as required by the rules of the teacher certification program in 2012; b) the instructors based of subject are distributed unevenly, some instructors have different education background with the subject they taught, and have not master level of education, while the need for eligible instructors is very urgent; c) the program curriculum has implemented the rules stated in the Buku IV Sertifikasi Guru dalam Jabatan Tahun 2012; d) the infrastructures are generally adequate. Things need to be put attention are the comfortable study rooms, clean toilets, and praying rooms; 3) On the Process component, the program implementation has been done by the rules of the teacher certification program in 2012. Things need to be put attention are to increase the relevant of the process in the classroom with the desired competencies required and the evaluation tool used in the written test on the last of the program; (4) on the Product component, it is acknowledged that the program participants have mastered personal and social competency up to 70% respondents, meanwhile pedagogic and professional competencies are under 70% respondents.Â